Analisis Pengaruh Luas Lahan, Produktivitas, Harga Beras, Harga Pupuk dan Harga Pestisida terhadap Kesejahteraan Petani di Kabupaten Tangerang - Bayu Eka Wicaksana (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2023)
Agriculture as the second largest supporting sector in the Indonesian economy has functioned as a provider of food, a provider of employment, and a source of community income. The need for staple food, especially rice, continues to increase along with the increase in population. The high conversion of agricultural land has become a threat to food security in Tangerang Regency. The strategy that needs to be carried out by the government is the availability of production land and the welfare of rice farmers. Farmer's Exchange Rate is an indicator used to measure farmers' welfare. This study aims to analyze rice farmers’ exchange rate and the effect of variables on land area, productivity, rice prices, fertilizer prices, and pesticide prices on the welfare of rice farmers in the Tangerang Regency. The research method used is Farmer's Exchange Rate Analysis and Multiple Linear Regression. Farmer's Exchange Rate is the ratio of the price of Laspeyers or the comparison of the price index received by farmers with the price index issued by farmers. Multiple Linear Regression to determine the effect of variables on land area, productivity, rice prices, fertilizer prices, and pesticide prices on the welfare of rice farmers. The results showed that the exchange rate of rice farmers in Tangerang Regency in 2021 experienced a significant decline. This is due to the Covid-19 pandemic which has increased the prices of farmers' consumer goods. Variables of land area, rice price, fertilizer price, and pesticide price significantly affect farmers' welfare.